2018
DOI: 10.1016/j.jpeds.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Validation of a Clinical Prediction Model for Congenital Diaphragmatic Hernias

Abstract: We successfully validated the CDHSG prediction model using an external population-based cohort of newborns with CDH in California. This cohort may be used to investigate hospital volume-outcome relationships and guide policy development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
1
24
2
Order By: Relevance
“…Several studies have created postnatal mortality-predictive models. The Congenital Diaphragmatic Hernia Study Group model is based on birth weight, 5 min Apgar, pulmonary hypertension, major cardiac defects and chromosomal anomalies, and the Wilford Hall/Santa Rosa equation is based on blood gas measurements 19–21. To date, no studies have examined tidal volumes (Vt) of spontaneous breaths in the first minutes after birth as a predictive factor for adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have created postnatal mortality-predictive models. The Congenital Diaphragmatic Hernia Study Group model is based on birth weight, 5 min Apgar, pulmonary hypertension, major cardiac defects and chromosomal anomalies, and the Wilford Hall/Santa Rosa equation is based on blood gas measurements 19–21. To date, no studies have examined tidal volumes (Vt) of spontaneous breaths in the first minutes after birth as a predictive factor for adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we externally validated the CDHSG rule in the European population. We found that the rule had fair discrimination, but also room for optimization, compared with the internal validation of Brindle et al 15 Bent et al 16 also validated the rule in a large group of patients with CDH born in California and found an underestimation of mortality in the patients with a score of 1. We did not find this in our population.…”
Section: Discussionmentioning
confidence: 59%
“…Validation of the prediction rule revealed reasonable discrimination between groups. 15,16 This postnatal model has been favorably compared with prenatal predictors. 17 However, there is potential value in combining postand prenatal risk factors within a single prediction model.…”
Section: What This Study Adds: We Validated the Congenital Diaphragmaticmentioning
confidence: 99%
“…This CDH scoring equation includes five predictors: 5 min Apgar, birth weight, PH, chromosomal anomalies and major cardiac defects 44. External validation has confirmed good performance and discrimination among the three groups 45…”
Section: Delivery Room Management: Novel Conceptsmentioning
confidence: 94%